Photoluminescence assessment of materials for solar cell absorbers. (5th August 2022) - Siebentritt, Susanne; Rau, Uwe; Gharabeiki, Sevan; Weiss, Thomas P.; Prot, Aubin; Wang, Taowen; Adeleye, Damilola; Drahem, Marwan; Singh, Ajay
Abstract : Photoluminescence is used to predict the open circuit voltage. However, band gap fluctuations and tail states broaden the PL emission and can lead to underestimation of the quasi Fermi level splitting. We discuss potential errors and how to avoid them. Abstract : Absolute photoluminescence measurements present a tool to predict the quality of photovoltaic absorber materials before finishing the solar cells. Quasi Fermi level splitting predicts the maximal open circuit voltage. However, various methods to extract quasi Fermi level splitting are plagued by systematic errors in the range of 10–20 meV. It is important to differentiate between the radiative loss and the shift of the emission maximum. They are not the same and when using the emission maximum as the "radiative" band gap to extract the quasi Fermi level splitting from the radiative efficiency, the quasi Fermi level splitting is 10 to 40 meV too low for a typical broadening of the emission spectrum. However, radiative efficiency presents an ideal tool to compare different materials without determining the quasi Fermi level splitting. For comparison with the open circuit voltage, a fit of the high energy slope to generalised Planck's law gives more reliable results if the fitted temperature, i.e. the slope of the high energy part, is close to the actual measurement temperature. Generalised Planck's law also allows the extraction of a non-absolute absorptance spectrum, which enables a comparison between the emission maximum energy and the absorption edge. We discuss the errors and the indications when they are negligible and when not.